KRAA. POERBONEGORO TOKOH KEPAHLAWANAN MASYARAKAT AMBAL: ANALISIS SKEMA AKTAN DAN FUNGSIONAL SERTA FUNGSI LEGENDA KEBUMEN - -, Haryanto -; Muhtarom, Imam; Hartati, Dewi (Peneliti.net, 2024)
This study analyzes the structure and function of telling the legend of KRAA. Poerbonegoro which developed in Ambal District, Kebumen Regency, Central Java. This legend tells of the heroism of a KRAA. Poerbonegoro who put down the mastermind behind the riots and robbery of agricultural products in the Urut Sewu Region, namely Puja Gamawijaya. for the struggle of KRAA. Poerbonegoro, the mastermind behind the riots in the Urut Sewu area, could be killed. So that in the end, KRAA. Poerbonegoro received the title of duke of Ambal by the Dutch Government. The aim of this study is to explore the structure and function of the KRAA legend. Poerbonegoro in Benerwetan Village, Ambal District, Kebumen Regency. The research method uses descriptive qualitative methods, ethnographic approaches, and studies of oral traditions. The research data is in the form of KRAA legend stories. Poerbonegoro obtained through interviews with two informants. Data collection techniques include observation, interviews, recording, photographing, recording, transcription, and translation. The research stages included the pre-field stage of observing and seeking informants, the field work stage carrying out the data collection process, and the research completion stage carrying out the process of transcribing the data into written form, translating data from the informant's language into Indonesian, conducting an analysis of the actan structure and function of each story variants, analyzing the functions of each story variant, and discussing structure and function. The results showed the actan structure and function in both variants of the KRAA legend. Poerbonegoro concludes that having a connection or connection between actan and functional structures provides support for the flow of events that occur in the story. Characters or actors who fill in each room with certain functions and roles in the story. Meanwhile, in the function study shows. First, each variant is a projection function in society that is the legend of KRAA. Poerbonegoro is an illustration to the public that people's view of life is how life can be peaceful, harmonious, and not rioting. So that no community groups are harmed. Second, as a function of a tool for validating cultural institutions and institutions for each variant, informants said that the existence of the KRAA legend. Poerbonegoro took part in the culture in society with the aim of acquiring learning values. Third, the function as an educational tool is that each variant of the legend contains lessons that can be taken by the community, both from historical knowledge, heroic character, the principle of cooperation, and creating a harmonious life in society. Fourth, on the function of being a tool for coercing and controlling societal norms in each variant, the informant said that the legend of KRAA. Poerbonegoro provides an overview to the community in terms of acting in society so that stability and harmony in life can occur.